IMPROVING THE STUDENTS SPEAKING ACHIEVEMENT BY APPLYING FISHBOWL TECHNIQUE - Sri - Duinaria; Sumarsih - - (Universitas Negeri Medan, 2014)
Abstract The objective of this study is to find out whether Fishbowl Technique can improve students’ Achievement in speaking. This study was conducted by using classroom action research. The subject of this research was the second year students of SMA N 1 STTU Julu. The research was conducted in two cycles. The first cycle was three meetings and the second cycle was two meetings. The instruments for collecting data used speaking test for quantitative data and diary notes, questionnaires sheet, interview and observation sheet used for qualitative data. Based on the speaking test result, the students’ score kept improving in every test. In orientation test, the mean score was 46,05. In the test of cycle 1 the mean score was 60,05 and the mean score in the test of cycle 2 was 70,9. In line with the data, it was found that the fishbowl technique can improve students’ speaking achievement. Key Words : Speaking, Fishbowl Technique, Test, Data, Classroom Action Research